Beach morphodynamic classification using high-resolution nearshore bathymetry and process-based wave modelling. (5th May 2022) - Jackson, D.W.T.; Short, A.D.; Loureiro, C.; Cooper, J.A.G.
Abstract: Classification of beach morphodynamic state relies on accurate representation of breaking wave conditions, Hb (plus grain size and spring tidal range). Measured breaking wave data, however, are absent from all but a handful of sites worldwide. Here, we apply process-based wave modelling for propagating offshore waves to the breaking zone using high-resolution nearshore bathymetry, obtaining representative and accurate Hb values for multiple beaches at regional scale, and thereby derive meaningful morphodynamic classifications that accord with observed beach state. Ninety-five beaches on the north coast of Ireland were investigated, with observed beach types and states compared to predictions based on morphodynamic parameters determined using wave, tide and sediment data, obtained from field surveys and detailed numerical wave modelling. The coast is exposed to micro-through meso-tides (0.43–3.90 m) and low sea through high swell waves (Hb  = 0.13–1.18 m) and is composed of fine to medium sand resulting in a full range of beach types (wave-dominated, tide-modified and tide-dominated) and most beach states, thereby providing a comprehensive field laboratory to undertake such a comparison. We found that modal beach types reside within their predicted Relative Tide Range (RTR) and modal beach states close to the predicted dimensionless fall velocity (Ω) range. The use of high-resolution nearshore wave modelling to determine Hb was deemed the most appropriate approach for deriving predicted beach classification. The work follows the investigation of the same coast by Jackson et al. (2005) who found shortcomings in relating beach types to breaker wave conditions. However, advances in inshore wave modelling and access to high-resolution nearshore bathymetry since then have enabled improved estimates of breaker height, producing more accurate results and enhancing previous work. The results highlight the need to obtain accurate estimates of Hb and Tp if they are to be used effectively in predicting beach parameters. This work therefore sets a precedence for other coastal sites worldwide where detailed nearshore bathymetry is available and Hb can be derived from process-based wave modelling, improving the classification and prediction of morphodynamic beach type and state. Highlights: Wave modelling using detailed bathymetry improved beach classification accuracy. SWAN-derived breaking waves produced good agreement between observed and predicted beaches. Ireland's northerly beaches have wave- to tide-dominated beach classifications.